Primigravida dengan twin to twin transfusion syndrome - Balqist Ar Rahmah; Fonda Octarianingsih Shariff (THE JOURNAL OF Mother and Child Health Concerns, 2024)
The patient came to the emergency department at Bintang Amin Hospital with G1P0A0, 33 weeks pregnant with tight abdominal pain since 1 week ago. The patient said she felt nauseous and that the patient was pregnant with twins. Blood mucus (-), water-water (-). First menstruation at the age of 12 years, menstruation lasts 4-5 days, patient changes sanitary napkins 3 times a day. On physical examination, vital signs were found including blood pressure 110/60 mmHg, pulse 126 x/minute, respiratory rate 20 x/minute, temperature 36.5 °C, oxygen saturation 99%. On external examination DJJ: A. 155x/minute, B: 157x/minute, TFU: 40cm, HIS: 2x10'20'', internal examination of vaginal tocher no opening. On hematological investigations, a decrease in hemoglobin was found to be 11.4 g/dl, a decrease in hematocrit of 34%, a decrease in MCV of 74 fl and MCH of 25 pg. On ultrasound examination, A: BPD: 8.42 cm, HC: 27.90 cm, AC: 29.33 cm, FL: 6.69cm, EFW1: 2288g, B: BPD: 7.22 cm, HC: 27.52 cm, AC: 29.60 cm, FL: 4.73 cm, EFW2: 1598 g. The diagnosis in this case is primigravida with twin-to-twin transfusion syndrome. The treatment received by the patient was IVFD RL 20 tpm + protein drip 1 amp/8 hours, dexamethasone 2x2amp, cefazolin 2x1gr/iv, pronalges supp 2 extra. The prognosis in this patient is dubia. Keywords: Gemelli; Pregnant; TTTS. Pasien datang ke UGD Rumah Sakit Bintang Amin dengan G1P0A0 hamil 33 minggu dengan keluahan perut terasa kencang sejak 1 minggu yang lalu. Pasien mengatakan terasa mual dan pasien hamil kembar. Lendir darah (-), air-air (-). Haid pertama pada umur 12 tahun, haid selama 4-5 hari, pasien ganti pembalut sebanyak 3x sehari. Pada pemeriksaan fisik didapatkan tanda-tanda vital diantaranya tekanan darah 110/60 mmHg, denyut nadi 126 x/menit, laju pernapasan 20x/menit, suhu 36,5 °C, saturasi oksigen 99%. Pada Pemeriksaan luar DJJ: A. 155x/menit, B: 157x/menit, TFU: 40cm, HIS: 2x10’20’’, pemeriksaan dalam vaginal tocher belum ada pembukaan. Pada pemeriksaan penunjang hematologi didapatkan penurunan hemoglobin dengan 11,4 g/dl, penurunan hematokrit 34 %, penurunan MCV 74 fl dan MCH 25 pg. Pada pemeriksaan USG didapatkan A: BPD: 8.42 cm, HC: 27.90 cm, AC: 29.33 cm, FL: 6.69cm, EFW1: 2288g, B: BPD: 7.22 cm, HC: 27.52 cm, AC: 29.60 cm, FL: 4.73 cm, EFW2: 1598 g. Diagnosis pada kasus ini yaitu primigravida dengan twin to twin transfusion syndrome. Tatalaksana yang didapat oleh pasien yaitu IVFD RL 20 tpm + proterin drip 1 amp/8jam, dexametason 2x2amp, cefazolin 2x1gr/iv, pronalges supp 2 extra. Prognosis pada pasien ini yaitu dubia. Kata Kunci: Gemelli; Hamil; TTTS.